Barriers to financial innovation: Corporate finance perspective - Joanna Błach (Journal of Risk and Financial Management, 2020)
This paper addresses the application of financial innovations from the corporate finance perspective. The objective is to identify and prioritize the main types of barriers to the implementation of financial innovations by nonfinancial firms. The motivation behind the study lies in the importance of financial innovations for the firms' ability to create value. As proven by the extensive literature review, comprehensive studies on financial innovation applications by nonfinancial firms are relatively rare. To cover this cognitive gap, the theoretical argumentation followed by the discussion of results of the empirical research are presented in this paper. The paper provides the results of two-stage survey research, aiming to find opinions of financial managers (end-users) and experts (creators of innovation) on the main barriers to financial innovations in Poland. According to managers, the most important are exogenous barriers, including: (1) Unclear tax and accounting regulations, (2) complex construction of financial innovations, and (3) transaction costs related to their application. On the other side, the experts from financial institutions recognized the greater importance of endogenous factors such as: (1) Lack of sufficient knowledge about financial innovations and (2) the reluctance to change observable in many firms. This study contributes to the ongoing debate on financial innovations by adding the perspective of corporate financial strategy. It also offers insights into the potential actions (at the institutional and individual level) aiming to reduce the barriers and support the implementation of financial innovations by nonfinancial firms.
Keywords: 330; barriers to innovations; corporate finance; financial innovations; financial strategy